In vitro activities of piperaquine, lumefantrine, and dihydroartemisinin in Kenyan Plasmodium falciparum isolates and polymorphisms in pfcrt and pfmdr1. - Mwai, L; Kiara, S; Abdirahman, A; Pole, L; Rippert, A; Diriye, A; Bull, P; Marsh, K; Borrmann, S; Nzila, A (2009)
We have analyzed the in vitro chemosensitivity profiles of 115 Kenyan isolates for chloroquine (CQ), piperaquine, lumefantrine (LM), and dihydroartemisinin in association with polymorphisms in pfcrt at codon 76 and pfmdr1 at codon 86, as well as with variations of the copy number of pfmdr1. The median drug concentrations that inhibit 50% of parasite growth (IC(50)s) were 41 nM (interquartile range [IQR], 18 to 73 nM), 50 nM (IQR, 29 to 96 nM), 32 nM (IQR, 17 to 46 nM), and 2 nM (IQR, 1 to 3 nM) for CQ, LM, piperaquine, and dihydroartemisinin, respectively. The activity of CQ correlated inversely with that of LM (r(2) = -0.26; P = 0.02). Interestingly, parasites for which LM IC(50)s were higher were wild type for pfcrt-76 and pfmdr1-86. All isolates had one pfmdr1 copy. Thus, the decrease in LM activity is associated with the selection of wild-type pfcrt-76 and pfmdr1-86 parasites, a feature that accounts for the inverse relationship between CQ and LM. Therefore, the use of LM-artemether is likely to lead to the selection of more CQ-susceptible parasites.